THE IMPACT OF SHIFT-WORK ON NUTRITIONAL STATUS OF POLICE OFFICERS - Ćopić, Nemanja Z.; Kukić, Filip; Tomić, Ivan; Parčina, Ivana; Dopsaj, Milivoj (NBP. Nauka, bezbednosti, policija, 2020)
Summary: The aim of this study was to show the extent of the influence of the shift work on nutritional status and physical activity of police officers. The research included 130 healthy police officers. The respondents were divided into two groups. The first group included 82 officers who were working the first shift. The second group included 48 officers who were working the shift of 12 hours. The study used customized questionnaire consisting of questions regarding leisure-time physical activity, self-report lifestyle activity level, body height, body mass, and derived body mass index (BMI). The ANOVA analysis showed that the First shift had significantly lower BMI (2.57 kg/m2, p=0.004) than the Shift of 12h. The results showed that physical activity had negative impact on BMI on both groups (p<0.01). Regarding the correlation between age and years of service, only the 12h Shift showed coherency (p<0.01). Although there was no difference in the level of physical activity between police officers from different shifts, their BMI was negatively statistically associated with indicators of physical activity.